SELF-REGULATED LEARNING PADA FLIPPED CLASSROOM DALAM PEMBELAJARAN DASAR: ANALISIS BIBLIOMETRIK - Alfahral, Reza; Hidasia, Muhammad Marsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the era of digitalization and globalization, higher education is required to develop learning methods that can enhance student learning independence. Self-Regulated Learning (SRL) is one of the essential skills that contribute to student academic success, especially in innovation-based learning such as the Flipped Classroom. This learning model reverses the traditional concept by providing access to materials before class and allocating face-to-face meeting time for discussion and problem-solving. However, there are still limitations in research specifically examining the relationship between the Flipped Classroom and the development of SRL, especially in the context of teacher education. This study aims to analyze the development of studies related to the Flipped Classroom and Self-Regulated Learning using a bibliometric approach based on Scopus data. Using VOSviewer and Mendeley Desktop software, this study identified publication trends, patterns of scientific collaboration, and emerging topics in these studies. The analysis results show that the number of publications related to the Flipped Classroom and SRL has increased significantly in recent years. Furthermore, this study also revealed that the integration of the Flipped Classroom model can strengthen students' self-regulation skills by increasing motivation, independent learning strategies, and active engagement in learning. This study is expected to contribute to academics, education practitioners, and policymakers in designing innovative, evidence-based learning methods that can improve SRL in higher education settings, particularly for pre-service teachers. Furthermore, this research also identifies potential areas for further exploration regarding the effectiveness of Flipped Classrooms in various educational contexts.